2018
DOI: 10.1007/s00167-018-5113-1
|View full text |Cite
|
Sign up to set email alerts
|

Good outcomes at mid-term following the reconstruction of chronic Achilles tendon rupture with semitendinosus allograft

Abstract: Case series, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Open and minimally invasive techniques using a semitendinosus graft, both allograft and autograft, have been described [ 14 , 22 , 25 , 36 , 40 , 43 ]. Those studies report ATRS scores between 86 and99.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Open and minimally invasive techniques using a semitendinosus graft, both allograft and autograft, have been described [ 14 , 22 , 25 , 36 , 40 , 43 ]. Those studies report ATRS scores between 86 and99.…”
Section: Discussionmentioning
confidence: 99%
“…Semitendinosus tendon graft is routinely used in knee surgery for ligament reconstructions and it has also been shown to have good outcomes when used to treat chronic ATR [ 22 , 35 , 40 ]. Most of these studies have involved open reconstructions performed through a large single incision, with potential wound healing complications as reported for repairs of acute ruptures [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been proven that better repair effects through external implementation of growth factor and/or stem cell therapy (during the tendon healing) can be achieved [ 22 ]. Several authors presented restoration of full function of the operated Achilles tendon and the overall patient satisfaction when using semitendinosus tendon grafts [ 18 , 23 , 24 , 25 ] or gracilis tendon grafts [ 26 , 27 ]. However, to our knowledge, this is the first study which presents a detailed, versatile clinical, functional and isokinetic assessment of patients after Achilles tendon reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge, this is the first study which presents a detailed, versatile clinical, functional and isokinetic assessment of patients after Achilles tendon reconstruction. Multiple assessments, which described the outcomes of the Achilles reconstruction were based on two most popular subjective, patient-reported scales: Achilles tendon Total Rupture Score (ATRS) and American Orthopedic Foot and Ankle Society Score (AOFAS), combined with isokinetic tests or functional tests [ 15 , 16 , 17 , 18 , 19 , 22 , 23 , 24 , 25 , 26 , 27 ]. However, in these studies, a clear contradiction was observed between the subjective and the objective outcomes, which, in our opinion, might be the result of an insufficient number of the Achilles tendon parameters tested.…”
Section: Discussionmentioning
confidence: 99%
“…5,37 However, it has frequently been adapted as a research tool in injuries of other joints, including injuries of the Achilles tendon. 9,16,21,24,25,28,[33][34][35] Although the validity of the Tegner scale for use in patients with Achilles injuries rather than ligamentous knee injuries is less clearly defined, the tool has precedent in the literature and was the best tool available commonly used for quantifying sport and activity levels in lower extremity sports injuries. The study's retrospective design required patient recall of their preinjury Tegner activity level.…”
Section: Discussionmentioning
confidence: 99%